Protests and persuasion: Partisanships effect on evaluating nonviolent tactics in the United States. (January 2023) - Croco, Sarah E; Cunningham, Kathleen Gallagher; Vincent, Taylor
How does the public respond to nonviolent resistance tactics? This survey experiment examines both approval and perceptions of legitimacy for five nonviolent tactics using a sample of American adults. We include two variations in our treatment – first examining responses to different protest tactics, then adding in the factor of co-partisanship, which we argue is a relevant identity in the US political context. In the non-partisan treatments, we find a stark dichotomy between our measures of approval and legitimacy. All nonviolent treatment tactics decrease approval for the neutral activist group using them, but three of four tactic treatments increase the probability that respondents will support our legitimacy indicators (congressional hearing invitation and media attention). We find that partisanship conditions how respondents evaluate nonviolent tactics of resistance, but not in ways we would expect based on the conventional wisdom that liberals favor 'nonviolent resistance' while conservatives do not. Partisan alignment has a consistent effect on respondent approval of tactics in that the partisan treatment leads to disapproval of out-partisan groups across the nonviolent tactics (compared to no mention of tactic or partisanship). Surprisingly, however, this finding on co-partisanship does not extend to our measures of legitimacy. Partisanship clearly conditions the way that respondents evaluate nonviolent tactics of resistance, but not necessarily in predictable ways.